NSAID Exposure and Risk of Alzheimer's Disease: An Updated Meta-Analysis From Cohort Studies - Zhang, Caixia; Wang, Yan; Wang, Dongyin; Zhang, Jidong; Zhang, Fangfang (Frontiers in Aging Neuroscience, 2018)
Background Initial observational studies and a systematic review published recently have suggested that nonsteroidal anti-inflammatory drug (NSAID) use has the trend to be associated with reduced risk of Alzheimer's disease (AD), while results remain conflicting. Thus we performed an updated meta-analysis to reevaluate the evidence on this association. Methods Data sources from PUBMED, Embase and Cochrane Library from inception through April 2017 were searched by two independent reviewers. Eligible cohort studies were selected according to predefined keywords. We did a meta-analysis of available study data using a random-effects model to calculate overall relative risks (RRs) for associations between NSAID exposure and AD risk. Results From 121 potentially relevant studies, 16 cohort studies including 236022 participants, published between 1995 and 2016, were included in this systematic review. Meta-analysis demonstrated that current or former NSAID use was significantly associated with reduced risk of AD (RR, 0.81, 95% CI0.70 to 0.94) compared with those who did not use NSAIDs. This association existed in studies including all NSAID types, but not in aspirin (RR, 0.89, 95% CI 0.70 to 1.13), acetaminophen (RR, 0.87, 95% CI 0.40 to 1.91) or non-aspirin NSAID (RR, 0.84, 95% CI 0.58 to 1.23). Conclusions Current evidence suggests that NSAID exposure might be significantly associated with reduced risk of AD. However, further large-scale prospective studies are needed to reevaluate this association, especially the associations in individual NSAID type.